Is Cupressus sempervirens native in Italy? An answer from genetic and palaeobotanical data - F. BAGNOLI; G. G. VENDRAMIN; A. BUONAMICI; A. G. DOULIS; S. C. GONZÁLEZ‐MARTÍNEZ; N. LA PORTA; D. MAGRI; P. RADDI; F. SEBASTIANI; S. FINESCHI (Molecular Ecology, 2009)
This study represents the first large‐scale analysis using nuclear molecular markers to assess genetic diversity and structure of Cupressus sempervirens L.. Genetic and fossil data were combined to infer the possible role of human activity and evolutionary history in shaping the diversity of cypress populations. We analysed 30 populations with six polymorphic nuclear microsatellite markers. Dramatic reductions in heterozygosity and allelic richness were observed from east to west across the species range. Structure analysis assigned individuals to two main groups separating central Mediterranean and eastern populations. The two main groups could be further divided into five subgroups which showed the following geographical distributions: Turkey with the Greek islands Rhodes and Samos, Greece (Crete), Southern Italy, Northern Italy, Tunisia with Central Italy. This pattern of genetic structure is also supported by samova and Barrier analyses. Palaeobotanical data indicated that Cupressus was present in Italy in the Pliocene, Pleistocene and Holocene. Furthermore, our molecular survey showed that Italian cypress populations experienced bottlenecks that resulted in reduced genetic diversity and allelic richness and greater genetic differentiation. Recent colonization or introduction may also have influenced levels of diversity detected in the Italian populations, as most individuals found in this range today have multilocus genotypes that are also present in the eastern range of the species. The data reveal a new interpretation of the history of cypress distribution characterized by ancient eastern populations (Turkey and Greek islands) and a mosaic of recently introduced trees and remnants of ancient, depauperate populations in the central Mediterranean range.